2021
DOI: 10.1097/md.0000000000026692
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose levels in chest computed tomography scans of coronavirus disease 2019 pneumonia

Abstract: To investigate computed tomography (CT) diagnostic reference levels for coronavirus disease 2019 (COVID-19) pneumonia by collecting radiation exposure parameters of the most performed chest CT examinations and emphasize the necessity of low-dose CT in COVID-19 and its significance in radioprotection.The survey collected RIS data from 2119 chest CT examinations for 550 COVID-19 patients performed in 92 hospitals from January 23, 2020 to May 1, 2020. Dose data such as volume computed tomography dose index, dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…The calculated median value of an effective dose E (2.6 mSv) is below the value reported by Zhou et al 4.55 mSv, but above the values reported for low-dose computed tomography examinations such as 0.28 mSv by Agostini et al, 1.3 mSv by Stuewe et al and 0.56 mSv by Dangis et al [ 34 , 38 , 42 , 46 ]. It is important to point out that in these studies the effective dose was calculated using the conversion factor and the DLP value, while we calculated the effective dose in the CTVoxDos program.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The calculated median value of an effective dose E (2.6 mSv) is below the value reported by Zhou et al 4.55 mSv, but above the values reported for low-dose computed tomography examinations such as 0.28 mSv by Agostini et al, 1.3 mSv by Stuewe et al and 0.56 mSv by Dangis et al [ 34 , 38 , 42 , 46 ]. It is important to point out that in these studies the effective dose was calculated using the conversion factor and the DLP value, while we calculated the effective dose in the CTVoxDos program.…”
Section: Discussioncontrasting
confidence: 61%
“…Zhou et al collected dose data from 92 hospitals for 550 patients. The median value for DLP was 325.2 mGy cm with a range of 6.79–1098 mGy cm, and the median value for CTDI vol was 9.68 mGy, with a range of 0.62–33.80 mGy for scanning protocols in Chonqing, China [ 38 ]. These data are significantly higher than those in our study, but it is important to note that these were doses collected from 92 different hospital centers with different scan parameters and different CT devices.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also reported more than one CT scan for Covid-19 patients. For instance, Zhou et al reported an average of 4 ± 2 CT scans for each patient with the median cumulative effective dose of 17.34 mSv between the range of 2.05–53.39 mSv ( Zhou et al, 2021 ). In another study by Cristofaro et al, the median total cumulative dose was 9.04 mSv ( Cristofaro et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering Table 4 of this study, 75th percentile of DRLs (79.25–437.80 mGy cm) shows that the values are in the range of these DRLs. However, in pandemics such as Covid-19, the CT scan is used for screening or follow-up, and it is recommended to use a low or ultra-low-dose, single-phase, fast-scan protocol ( Zhou et al, 2021 ); that the DLPs can be significantly lower. In this study, the least 75th percentile of DLPs for a multidetector spiral CT scanner equipped with IR was 79.25 mGy cm which is much smaller than DRL suggested by Paulo et al or European Commission, and the least 75th percentile of DLPs for a 4 slice, helical, CT scanner and filtered back projection reconstruction was 147.05 mGy cm which is again smaller than the lower boundary of DRL that were suggested in the mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…One downfall of CT scanning is radiation dose. In a study by Zhou et al (2021) [11], chest CT was performed an average of four times on 550 COVID-19 patients during hospitalization, yielding a median effective does (ED) of 17.34 mSv (range, 2.05-53.39 mSv). This is more than 17 times the yearly limit on radiation exposure to a single member of the public [12].…”
Section: Introductionmentioning
confidence: 99%